Fence. Volume four, Rivals - Pacat, C. S. (BOOM! Box, 2020)
Nicholas, Seiji, and the fencing team of the high-class Kings Row private school seem to be coming together, bonding as more than teammates, when their deadly rival, the MLC school, becomes their challenger in the State Championships. Seiji and Nicholas will have to learn to work together instead of competing for the spotlight, or else this year's game will go just as badly as last year.